Depressive symptoms and perceived chronic stress predict test anxiety in nursing students - Christoph Augner (University of Ostrava, 2015)
Aim: The aim of this study is to identify predictors of test anxiety in nursing students. Design: Cross sectional pilot study. Methods: A questionnaire was administered to 112 students of an Austrian nursing school (mean age = 21.42, SD = 5.21). Test anxiety (measured by the standardized PAF Test Anxiety Questionnaire), perceived chronic stress, depressive symptoms, pathological eating and further psychological and health parameters were measured. Results: We found highly significant correlations between test anxiety and working hours (0.25), depression score (0.52), emotional stability (-0.31), and perceived chronic stress (0.65) (p < 0.01, for all). Regression analysis revealed chronic stress and emotional instability as best predictors for test anxiety. Furthermore, path analysis revealed that past negative academic performance outcomes contribute to test anxiety via depressive symptoms and perceived chronic stress. Conclusion: Depressive symptoms and perceived chronic stress are strongly related to test anxiety. Therefore therapy and training methods that address depressive symptoms and perceived chronic stress, and thereby aim to modify appraisal of potential stressful situations, may be successful in addressing test anxiety.